Fish farming in cages: A practice to be restricted in Brazil - Camargo, Antonio Fernando Monteiro [UNESP]; Amorim, Rafael Vieira [UNESP] (FapUNIFESP (SciELO), 2020)
World aquaculture has been growing sharply in recent decades and Brazilian production of fish in cages has grown considerably since the end of the 1990s. This increase is related to the development of federal government regulations and the large number of medium and large hydroelectric reservoirs. The main areas of fish production in cages in Brazil are currently located in the Northeast and Southeast regions and along the Southeast/South border. Tilapia production in cages in Brazil, as well as other species produced in cages in other regions of the world, has economic advantages for the producer. On the other hand, limnologically, tilapia production in cages causes enormous damage, as it promotes the process of artificial eutrophication and, possibly, introduces this exotic species. One way of reducing artificial eutrophication is the use of Integrated Multi-trophic Aquaculture (IMTA); however, its use in fish cages installed in Brazilian reservoirs is not possible yet. Therefore, our view is that government agencies restrict the production of fish in cages to the utmost.
Produção de peixes em tanques-rede: Uma prática a ser restrita no Brasil
Keywords: Artificial eutrophication; Brazilian reservoirs; Good management practices; Limnological negative impacts; Tilapia production